Stable sources of resistance to yellow rust and powdery mildew in Indian and exotic wheat germplasm - Sood, Tanvi; Basandrai, Daisy; Basandrai, Ashwani Kumar; Sohu, V S; Rana, Vijay; Mehta, Amritpal; Sharma, B K; Mavi, G S; Kaur, Jaspal; Bains, N S (Journal of Cereal Research, 2025)
Yellow rust (Puccinia striiformis f. sp. tritici) and powdery mildew (Blumeria graminis tritici) of wheat can be effectively managed by the cultivation of resistant varieties. However, such resistant varieties become susceptible due to evolution and spread of new and matching virulences of these pathogens after a short period of their commercial cultivation. Hence, breeding for disease resistance tends to be a continuous process with pre-requisite of identification of diverse resistant donors. In this context, more than 500 genotypes comprising advanced breeding material form CIMMYT and those developed in India were subjected to multilocational screening at hot spot locations of yellow rust and powdery mildew (Dhaulakuan, Malan and Ludhiana) under artificial epiphytotic conditions during the Rabi cropping season 2014-15 to 2016-17. Five genotypes from advanced Indian wheat breeding material were free from both the diseases whereas, 8 genotypes of CIMMYT origin showed mean terminal yellow rust (TYR) severity ≤5S and terminal powdery mildew (PM) reaction ≤3 and were highly resistant whereas 30 genotypes among Indian wheat breeding material showed mean terminal YR severity ≤5S and terminal PM reaction ≤5 were found resistant. Agronomically superior genotypes may be directly utilized as varieties and sources with multiple resistance may be used as donors in breeding program. DOI.10.25174/2582-2675/2020/100835